Student commitment to technology in times of COVID–19: public universities in southern Peru during the bicentenary of independence - Neira Ponce, Elsa Emma (2021)
Peru was no different to any other country in having to tackle Covid-19, but it did as it was preparing to celebrate the bicentenary of its independence. Great changes therefore had to be made to the celebrations as well as to other aspects of national life--especially the education sector, in which universities witnessed radical alterations to the teaching--learning process. Students had to learn using technology, despite often lacking the necessary equipment or being accustomed to other forms of learning behavior. Therefore, it is important to explore the extent to which students and their professors have been committed to the use of technology across different courses. Many studies have shown that academic engagement is a construct that encourages student learning, interest, well-being, and performance. However, a key problem in this line of enquiry involves determining the relationship between student commitment and the use of ICT in the learning process; these technologies are particularly important at present, even though some research has found that students only use it as a distraction. Therefore, in the present study we seek to determine the relationship between student commitments to learning and the technology they use in the process. In so doing we yielded an acceptable Spearman R correlation of 0.417, which indicates that there is in fact a correlation between the use of technologies and student engagement. This means that students are committed to technology even when their socio-economic levels mean they cannot afford to purchase these new tools. In turn, the information we collected alongside professors indicated a moderate correlation of 0.376, indicating that although professors are committed to teaching, they still do not have much of a relationship with technology and make limited use of it in the classroom. Thus, in sum, we found that students are closer to these forms of technology while their professors remain at a stage of adaptation.